Endometrial Stem Cells and Its Potential Applications - Somasundaram, Indumathi (SpringerBriefs in Stem Cells,, 2016)
Stem cells have ushered in widespread interest and exciting possibilities for cell based therapies. Despite multiple initiatives and meticulous untiring efforts, translating this bench side research into bedside practice and therapies remains a challenge. A better understanding of expanding research in specific areas of stem cells is crucial in developing regenerative medical therapeutics. With their unique attributes, studies on stem cells of endometrium and its therapeutic applications at both in-vitro and at pre-clinical settings in health and disease states are gaining consensus in recent years. This SpringerBrief provides a thorough but succinct presentation of solid information about the significance of stem cells from the endometrium, the inner lining of the uterus. It presents an understanding of stem cells derived from human endometrium and examine how cells from these sources are being used to research and therapeutics for various clinical problems and diseases. In addition, brief also discusses the threats and challenges facing endometrium. Overall, it illuminates the hope that, the stem cells of endometrium can be an effective source of therapeutics for a multitude of disorders.